2013
DOI: 10.33584/jnzg.2013.75.2904
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pasture renewal, soil factors and climate on black beetle abundance in Waikato and Bay of Plenty

Abstract: An outbreak of the sporadic pest black beetle caused major damage on farms throughout Waikato and Bay of Plenty regions from 2007 to 2010. Two projects were initiated in these regions to gain an understanding of the interaction of black beetle with endophyte/ cultivar combinations and pasture renewal strategies. Monitoring of black beetle populations on the project farms showed that overall, abundance steadily declined from 2009 to 2013, possibly due to cool temperatures, and in the case of Bay of Plenty, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…and Bell et al (2011) reported that substantial damage can be caused by populations as low as 20/m 2 . Gerard et al (2013) reported densities from five Bay of Plenty and two Waikato farms, measured from 2009 to 2013 ranging from 5 to 50 black beetles/m 2 . Using the mean level from that data set, of 21/m 2 , the costs would be $440 to $660/ha to dairy farmers, or $148 M to $223 M annually, and for sheep and beef farms $15.4 M to $18.9 M p.a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Bell et al (2011) reported that substantial damage can be caused by populations as low as 20/m 2 . Gerard et al (2013) reported densities from five Bay of Plenty and two Waikato farms, measured from 2009 to 2013 ranging from 5 to 50 black beetles/m 2 . Using the mean level from that data set, of 21/m 2 , the costs would be $440 to $660/ha to dairy farmers, or $148 M to $223 M annually, and for sheep and beef farms $15.4 M to $18.9 M p.a.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, warm late autumn and early spring temperatures reduce the period during which temperatures are too low for beetles to feed, which is also likely to increase their survival. Not surprisingly, therefore, region-wide outbreaks of black beetle have recently been linked with La Niňa events which result in warmer than normal spring and autumn temperatures over the northern North Island that can coincide with drought conditions (Gerard et al 2013).…”
Section: Life Cycle and Biologymentioning
confidence: 99%
“…17 In response to climate change, black beetle has become a chronic pest in northern North Island pastures, 18 and outbreaks of this pest are likely to become more frequent and its distribution is expected to expand. 19 Heteronychus arator is a good target for developing a biopesticide because current compounds are largely ineffective, so no chemical insecticides are registered for use against this pest in established pastures. 20,21 Neonicotinoid seed treatments (registered active ingredients are clothianidin and imidacloprid) can be used against H. arator in newly sown pasture and arable crops.…”
Section: Introductionmentioning
confidence: 99%
“…The primary strategy for controlling H. arator in New Zealand pastures is sowing ryegrass varieties with associated endophytes that confer resistance to herbivory ( Thom et al, 2014 ). These varieties limit H. arator populations, but outbreaks still occur, particularly during warmer La Niña years ( Bell et al, 2011 ; Gerard et al, 2013 ). No insecticides are registered for use against H. arator in New Zealand pastures, and results of insecticide experiments in Australia and New Zealand have been mixed ( Matthiessen and Learmonth, 1995 ; Bulinski and Matthiessen, 2002 ; Bulinski et al, 2006 ; Eden et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Population density can be measured by sampling either cores or spade squares of soil to count the number of individuals and converting them to numbers/m 2 ( Watson et al, 1980 ). When H. arator densities are high (>50 adults/m 2 ), this method is sufficiently sensitive to measure population responses to treatments, but when populations are low (typically 0–25 adults/m 2 ; Gerard et al, 2013 ), impractically high sample numbers are required to assess treatment effects within field plot experiments. Pitfall traps are commonly used to measure dispersal and spatial patterns in populations of ground dwelling beetles ( Matthiessen and Learmonth, 1998 ; Noronha and Cloutier, 1999 ; Negro et al, 2008 ; Elek et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%